E-WOM, PERSEPSI HARGA MENINGKATKAN KEPUASAN WISATAWAN MELALUI KEPUTUSAN BERKUNJUNG DI MUSEUM MACAN - Nadya Khoirrani; Parlagutan Silitonga (Human Capital Development, 2023)
The purpose of this study is to improve tourist satisfaction with E-wom and price perception through the mediating role of visiting decisions at Museum MACAN. The population in this study is visitors to the Tiger Museum during March 2023. The sampling technique used to determine was 170 respondents with Accidental Sampling. The data collection method uses questionnaires that are distributed to respondents, thus this research method is quantitative descriptive. The analysis used was using SmartPLS 3.0.The results showed that there was no significant effect of Ewom on direct tourist satisfaction. There was a significant influence of the Ewom on the decision to visit in person. There is a significant influence of Ewom on tourist satisfaction indirectly through visiting decisions. There is a significant influence of price perception on tourist satisfaction. There is a significant influence of price perception on visiting decisions.